Case report: Efficacy and safety of regorafenib plus fluorouracil combination therapy in the treatment of refractory metastatic colorectal cancer - Haque, Emaan; Muhsen, Ibrahim N.; Esmail, Abdullah; Umoru, Godsfavour; Mylavarapu, Charisma; Ajewole, Veronica B.; Abdelrahim, Maen (Frontiers in Oncology, 2022)
Background: More than half of patients with colorectal cancer (CRC) present with metastatic disease or develop recurrent disease on first-line and second-line options. Treatment beyond the second line remains an area of unmet need for patients with progressive or recurrent disease. Methods: We retrospectively reviewed data of adult (>18 years old) patients with mCRC who received regorafenib + 5FU combination therapy at Houston Methodist Hospital with outcomes of interest including response rate, discontinuation due to side effects, and overall survival. Results: Seven patients received regorafenib + 5FU combination therapy for mCRC after receiving at least two other lines of therapy (including at least one fluorouracil-based therapy). Four patients (57%) achieved disease control in 7-12 weeks after therapy initiation while three patients developed recurrent disease. In patients who achieved disease control, no new adverse events were reported among patients with this combination. Conclusion: Regorafenib and Fluorouracil combination could be considered an option beyond the second line for patients with treatment-refractory metastatic colorectal cancer. Further studies, including a prospective trial, are needed to investigate the efficacy and safety of regorafenib plus 5FU therapy compared to other limited available therapies.